KEBUTUHAN BELAJAR PESERTA PENDIDIKAN NONFORMAL (PNF) DAN IMPLIKASINYA TERHADAP KEMAMPUAN TENAGA KEPENDIDIKAN PNF - Soedijarto Soedijarto (Jurnal Ilmiah Visi, 2006)
Human basic needs according to Declaration for Education for All are needs (1) to survive; (2) to have an optimal self-development; (3) to participate in society development; (4) to get a job; (5) to make decisions based on information, and (6) to get an access to long life education. Those basic needs are important to determine the quality of life. Further, the quality of life of society itself would also affect the economic development of a nation regarding abilities (1) to manage natural resources, (2) to result high quality of commodity, (3) to develop technology, (4) manage capital flow, and (5) sell products. NFE as a part of national education systems plays an important role in improving the quality of life of society. NFE prepares society to be survival and qualified in responding to global challenges. It may conduct learning activities and programs as well as improve relevant learning resources and models, knowledge and skills of its educators and education personnel.